Uwarunkowania konkurencyjności żywności ekologicznej - Lewińska, Anna (Conditions of Organic Foods' Competition, 2006)
The aim of the paper is analysis of organic food customers' preferences in opposition to other food products. The research has been done on the example of inhabitants of West Pomerania who are consumers of organic food. The method of Analytic Hierarchy Process is used in the calculation of organic foods' competitive model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 34-39